FOOD INSECURITY AND ASSOCIATED FACTORS AMONG PUBLIC POLICIES BENEFICIARIES IN THE MUNICIPALITY OF PETROPOLIS-RJ, BRAZIL - Aline Gaudard e Silva; Cintia Chaves Curioni (Universidade do Estado do Rio de Janeiro, 2013)
Brazil produces enough food to feed its population. However, millions of Brazilians continue to suffer from hunger. To combat poverty and hunger, innovative programs have been launched by the government. This cross-sectional study aimed to investigate the prevalence of food insecurity (FI) among beneficiaries of two local programs to combat hunger: food supply (FS) and popular restaurant (PR) as well as to establish the association between food insecurity and some markers of social inequality. In the municipality of Petropolis-RJ, Brazil, 195 families that benefit from these programs were assessed to investigate the FI by the Brazilian Food Insecurity Scale (EBIA). Socioeconomic and demographic variables were also evaluated. The prevalence of FI was 42.9% in the families that benefit from PR and 72.2% in the families included in the FS program. The number of family members, presence of family members under 20 and 6 years, economic level, family monthly per capita income, race of the head of the family, home ownership, type of construction and number of rooms of the household were significantly associated with food insecurity (p<0.05). Ensuring food security demands crucial coordinated actions involving the appropriate linkage between the structural policies and emergency interventions. It is not an easy task, especially in Brazil, historically marked by social inequality. The results were important to identify the most vulnerable families that should be prioritized for assistance measures. The first step has been taken, but much more remains to be done. Simple tools such as EBIA can be used to monitor and combat inequality.